A prospective randomized trial comparing clomiphene citrate with metformin or a combination of both for ovulation induction in poly cystic ovarian Syndrome - Hasan, Sahar (Latakia University Journal -Medical Sciences Series, 2018)
AIM: To compare clomiphene citrate (CC), metformin or the combination of CC and metformin as the first line ovulation induction drug in infertility women with polycystic ovary syndrome (PCOS). METHODS: One hundred diagnosed, treatment naive PCOS women were recruited. They were randomized into any of the three groups: Group I (CC 50–150 mg/day), Group II (metformin 1700 mg/day), and Group III (CC + metformin in similar dosage to Groups I and II). Patients underwent follicular monitoring and advice on timed intercourse.. Secondary outcomes were ovulation rate, pregnancy rate. The study period was in ( 2016- 2017) Tishreen University Hospital . RESULTS: There was no significant difference among the groups in baseline characteristics and. Group III (CC + metformin) had the highest ovulation (75.76%), pregnancy (45.46%),. Group II (metformin) was as good as Group I (CC) in all the outcomes. CC + metformin (Group III) had statistically significantly higher ovulation rate as compared to CC alone (Group I) (P = 0.03) CONCLUSION: Thus, our study shows that metformin was as good as CC in terms of ovulation and pregnancy rate , the combination of CC and metformin gave the highest ovulation and pregnancyrate . دراسة ميدانية مقارنة بين سيترات الكلوميفين وميتفورمين ومشاركة المركبين معا في تحريض الإباضة عند مريضات متلازمة المبيض عديد الكيسات هدف الدراسة: مقارنة فعالية سترات كلوميفين وميتفورمين والمشاركة بين المركبين في تجريض الإباضة من حيث معدل حدوث الإباضة والحمل في حالات العقم المعزول الناتج عن اللاإباضة المزمنة عند المصابات بمتلازمة المبيض عديد الكيسات . أهمية الدراسة : أظهرت عديد من الدراسات فعالية عالية للكلوميفين في تحريض الإباضة ولكن يوجد مقاومة له عند اخريات ,ولذلك ظهرت دراسات حول فعالية المتفورمين للعلاج وحديثا أخرى أظهرت فعالية مهمة عند مشاركة المركبين معا في حدوث الإباضة والحمل بعد استخدامه في تحريض الإباضة . مكان البحث: المريضات المراجعات للعيادة النسائية في مشفى تشرين الجامعي بين عامي 2016- 2017 طرائق البحث : تجربة معمهة تشمل 100 مريضة لديها لا إباضة مزمنة مصابة بمتلازمة المبيض عديد الكيسات كسبب معزول للعقم |, قسمت المريضات إلى ثلاث مجموعات وأعطيت المريضات بطريقة عشوائية سترات كلوميفين (50-150 مع / اليوم ) أو متفورمين ( 1700 مع/اليوم ) أو الإثنين معا ( بنفس الجرعة ), لتحريض الإباضة من اليوم 5_9 من الدورة الطمثية .يتم إجراء ايكو عبر المهبل لمتابعة الاباضة لجميع المريضات وفي حال تأخر الطمث يجرى معايرة BHCG . استمرت المعالجة لست دورات أو حصول الحمل . النتائج : معدل حدوث الإباضة في المجموعة الأولى CC)) 42.8 % ,معدل حدوث الإياضة في المجموعة الثانية ميتفورمين 41.2% . عند المجموعة الثالثة التي عولجت بالمركبين معا كانت نسبة حدوث الإباضة 75.67%. معدل حدوث الحمل في المجموعة الإولى : 28.58% . معدل حدوث الحمل في المجموعة الثانية: 27.81 % . وفي المجموعة الثالثة 45.46% . الخلاصة : كما نلاحظ من النتائج فإن معدل حدث الإباضة والحمل كان أعلى بشكل واضح لدى المريضات اللواتي تمت معالجتهن بالمشاركة بين متفورمين وكلوميفين سترات مع فروق إحصائية هامة . وهكذا تشكل المشاركة بين المركبين لعلاج العقم عاملا أقوى في تحريض الإباضة من استخدام كل مركب على حده , وفقا لدراستنا . الدراسة الإحصائية : دراسة لنتيجة تحريض الإباضة كل دورة تكون بحساب معدل حدوث الإباضة ومعدل حدوث الحمل في كل من المجموعات الثلاث والعلاقة الإحصائية بينهم هي القيمة P ( Probability Value ) وتعتبر هذه القيمة هامة إحصائيا في حال كانت P< 0.05 .